TELAAH DINAMIKA RELASI ISLAM – INDONESIA: TINJAUAN HISTORIS DALAM PERSPEKTIF HUKUM: A Historical Review from a Legal Perspective - Aqshadigrama, Muhammad (Al Hikmah, 2025)
A legitimate government is formed through agreements between individuals in society to form a political community. The social contract theory initiated by Jean-Jacques Rousseau in his book states that humans do not only have individual wills, but there are common wills and interests to create a conducive situation. This research tries to examine the dynamics of the relationship between Islam and the Indonesian state within the framework of a legal perspective as an effort to maintain national unity. The approach used in this paper uses a descriptive method, which is combined with literature study as a data collection technique. The data is obtained from various literatures such as books, journals, as well as printed and digital sources of information that are considered relevant to explain the phenomenon that is the focus of this research. The dynamics of the position of Islamic law in Indonesia certainly changes over time until today, where Islamic law has its own sector and becomes a reference in the application of positive law in Indonesia. Muslims in Indonesia do not only have the interests of Islamic groups by prioritizing the application of Islamic law in Indonesia, but there is a spirit of togetherness with elements outside Islam to create peace and security in forming national unity. The social contract that occurs among Indonesian people is a factor that is quite influential in how the relationship between religion and the state in Indonesia at this time. This does not only happen in the legal field, but also in many aspects as an effect of the social contract that occurs.